Endoscopic and surgical management of anastomotic leakages following gastroesophageal cancer surgery: a systematic review and meta-analysis - Isabel Lopes Dias Azevedo (2021)
Background and objectives: Anastomotic leakage (AL) is one of the most feared postoperative complications of gastroesophageal surgery. AL can be managed by conservative, endoscopic (such as endoscopic vacuum therapy and stenting) or surgical methods, but optimal treatment remains controversial. The aim of our meta-analysis was to compare a) endoscopic and surgical interventions and b) different endoscopic treatments for AL following gastroesophageal cancer surgery. Methods: Systematic review and meta-analysis, with search in three on-line databases (MEDLINE, ISI Web of Knowledge and Scopus) for studies evaluating surgical and endoscopic treatments for AL following gastroesophageal cancer surgery. Results: A total of 32 studies comprising 1080 patients were included. Compared with surgical intervention, endoscopic treatment was associated with lower in-hospital mortality (35.8% [95% CI 23.9-48.5%] versus 6.4% [95% CI 3.8-9.6%]), although clinical success, hospital length of stay and intensive care unit (ICU) length of stay were similar in both groups. Compared with stenting, endoscopic vacuum therapy was associated with a lower rate of complications (OR 0.348 [95% CI 0.127-0.954]) and shorter ICU length of stay (mean difference -14.77 days [95% CI -26.57 to -2.98]) and time until AL resolution (17.6 days [95% CI 14.1-21.2] versus 39.4 days [95% CI 27.0-51.8]). There were no significant differences in terms of clinical success, mortality, reinterventions, and hospital length of stay. Conclusions: Endoscopic treatment (in comparison to surgical intervention) and endoscopic vacuum therapy (in comparison to stenting) are safer and more effective. However, more robust comparative studies are needed to confirm these benefits.